Adaptasi Alat Ukur Literasi Gizi Pada Mahasiswa Angkatan Pertama Program Sarjana Di Universitas Pattimura, Maluku - Yoseline Sopamena; Yulita Sirinti Pongtambing; Wa Ode Arin Sri Andriani; Yessy Fitriani; Dien Anshari (Departement of Nutrition, Faculty of Public Health, Hasanuddin University, Makassar, 2020)
Background: Nutrition literacy indicate the competence to earn, gather, understand, interpret and practice nutrition information to make proper health decision. Objective: To assess validation and reliability of modified-Newest Vital Signs (NVS) instrument. Method: Data collection divided into two phases: (1) Qualitative, where we conducted cognitive interview to 10 first year college students at Pattimura University using HLS-EU-Q16 for health literacy measurement, subsequently with NVS questionnaire which has 6 questions for nutrition literacy measurement that had been translated into Bahasa on previous research. Thereafter, (2) a quantitative survey (n=362) was performed for confirming the NVS against functional domain of HLS-EU-Q16. Result: Mean score for participants done the survey was 2,35 (SD 0,01). Spearman-P coefficient correlation between HLS-Q16 functional domain met the instrument validation standard (r=0,11, p-value=<0,001). Cronbach alpha was 0,590 indicating weak internal consistency. Conclusion: The Newest Vital Sign has validity to measure functional level of nutritional literacy of first year college students of Pattimura University.